Finite Element Modeling of One-Way Recycled Aggregate Concrete Slabs Strengthened using Near-Surface Mounted CFRPs under Repeated Loading (Journal of Engineering, 2022)
This study offers numerical simulation results using the ABAQUS/CAE version 2019 finite element computer application to examine the performance, and residual strength of eight recycle aggregate RC one-way slabs. Six strengthened by NSM CFRP plates were presented to study the impact of several parameters on their structural behavior. The experimental results of four selected slabs under monotonic load, plus one slab under repeated load, were validated numerically. Then the numerical analysis was extended to different parameters investigation, such as the impact of added CFRP length on ultimate load capacity and load-deflection response and the impact of concrete compressive strength value on the structural performance of slabs. This article aims to provide a numerical model for simulating the nonlinear behavior of such slabs, including a trustworthy finite element model approach and constitutive material models. In aspects of load-deflection and cracking patterns, comparisons between computational and experimental models are provided, and a reasonable fit is demonstrated. The average ratio of numerical model ultimate load and deflections to experimentally tested slabs were 0.992 and 0.913, respectively. As a result, finite element analysis may be regarded as a preferred and trustworthy approach for simulating the non-linear behavior of one-way slabs (strengthened or not) in terms of complexity, difficulty, time savings, human effort, and money.